DAHAGA: An Islamic spiritual mindfulness-based application to reduce depression among nursing students during the COVID-19 pandemic - Meidiana Dwidiyanti (Belitung Raya Foundation, 2021)
Background: The COVID-19 pandemic significantly impacts students’ mental health. Most of them may experience depression. Due to restrictions and social distancing during the pandemic, counseling may not be applicable in detecting the problems. Therefore, an Islamic spiritual mindfulness-based application called DAHAGA is created in order to detect and reduce depression. It is believed that this innovative app could reduce mental health problems among students.